Transnational Student Return Migration and Megacities in China Practices of Cityzenship - Wang, Zhe. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book is a study of the return migration of overseas Chinese students. By 2018, over 3.5 million Chinese students had returned from overseas universities to China, with the megacities of Beijing, Shanghai, and Shenzhen representing by far their main destinations. In other words, when overseas students return to China, many do not return to their hometown but usually land, work and settle down in Beijing, Shanghai and Shenzhen. Their return migration is thus not only transnational, but also internal-urban. This book adopts a multi-level geographical analysis to explore this important phenomenon, exploring why and how returnees choose these three cities and how they experience and interpret their everyday lives in these megacities after their return. In doing so, it highlights the importance of cultural logics and multiscalar thinking of transnational Chinese students' return migration and illuminates how their transnational migration reproduces domestic socio-spatial inequalities. This book brings an important contribution to the fields of Cultural Geography, Urban Geography, Transnationalism, Migration Studies and Citizenship Studies. Zhe Wang is a postdoctoral research fellow and a member of the Comparative and International Education Research Group in the Department of Education, University of Oxford. She has an interdisciplinary research background. Her research interests include international higher education, student (im)mobilities, transnational education space, urbanization and development.
Chapter 1 Introduction -- Chapter 2 Cityzenship: Contemporaneous Migration, City and Citizenship -- Chapter 3 To be a cityzen of where? -- Chapter 4 To live as a cityzen: class-based cosmopolitan cityzenship -- Chapter 5 Cityzenship and the Hukou System -- Chapter 6 A 'Modern' Cityzen -- Chapter 7 Conclusion.
Keywords: Human geography; Emigration and immigration; Emigration and immigration -- Social aspects; Education, Higher; Educational sociology; Sociology, Urban; Human Geography; Human Migration; Sociology of Migration; Higher Education; Sociology of Education; Urban Sociology